2006
DOI: 10.1007/11693017_31
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Code Clones and Change Couplings

Abstract: Abstract. Code clones have long been recognized as bad smells in software systems and are considered to cause maintenance problems during evolution. It is broadly assumed that the more clones two files share, the more often they have to be changed together. This relation between clones and change couplings has been postulated but neither demonstrated nor quantified yet. However, given such a relation it would simplify the identification of restructuring candidates and reduce change couplings. In this paper, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 19 publications
0
55
0
Order By: Relevance
“…Instead, we are primarily interested in identifying the evolution patterns of a set of clones detected in the software system (in a release) and relating the evolution pattern with other variables (clone radius, clone granularity, cloned code fault-proneness). By excluding new clone classes (or just new clone fragments) 21 occurring in future snapshots, we limit the age difference of clones we are considering in the study. is a free version of the SSH connectivity tools implemented in ANSI C and used to provide a secure channel between network connections.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, we are primarily interested in identifying the evolution patterns of a set of clones detected in the software system (in a release) and relating the evolution pattern with other variables (clone radius, clone granularity, cloned code fault-proneness). By excluding new clone classes (or just new clone fragments) 21 occurring in future snapshots, we limit the age difference of clones we are considering in the study. is a free version of the SSH connectivity tools implemented in ANSI C and used to provide a secure channel between network connections.…”
Section: Contextmentioning
confidence: 99%
“…The relationship between clones and change couplings has been examined by Geiger et al [21]. They proposed a framework to examine code clones and relate them to change couplings taken from release history analysis.…”
Section: Clone Genealogy and Tracingmentioning
confidence: 99%
“…Geiger et al showed some relations between code clones and logical couplings [32]. Since code clones cannot be fully captured by call dependencies and data dependencies, some parts of logical couplings are not covered by ImpactScale.…”
Section: Threats To Validitymentioning
confidence: 99%
“…Historical data on the changes of open-source systems allowed researchers to empirically investigate on the evolution of various software entities, such as clones [10,14] or design motifs [2]. Some studies considered changes between releases, i.e., stable snapshots released after some amount of changes, while others exploited the historical data available in versioning systems, such as CVS or SVN.…”
Section: Related Workmentioning
confidence: 99%